THE ROLE OF FINANCIAL MANAGEMENT AT MICRO ENTERPRISE TO IMPROVE PROFITABILITY IN SERANG - Yuliah, Yuliah; Triana, Leni (Yayasan Education and Social Center, 2025)
This study aims to examine the role of financial management in increasing the profitability of micro-enterprises in Serang City. The main focus of the study lies in four aspects of financial management, namely financial planning, financial recording, financial control, and financial evaluation. This study uses a qualitative approach with a field study method. Data were collected through in-depth interviews with micro-entrepreneurs in various sectors, as well as direct observation of financial management practices carried out. The results of the study indicate that financial planning has been carried out by most MSMEs, although in a simple form. This provides a positive contribution to cost efficiency and capital management. In terms of financial recording, business actors have started recording daily transactions, but it is still manual and has not been optimally digitized. Meanwhile, financial control is still a major weakness, marked by the mixing of business and personal funds, and the absence of a formal financial control system. Financial evaluation has also not become a routine habit, so business actors have difficulty in measuring the development and performance of their businesses objectively. The findings of this study emphasize the importance of increasing financial literacy and management practices for micro-entrepreneurs. Continuous training and mentoring are needed to strengthen financial functions that can drive increased profitability. This study contributes to the literature on MSME management and can be a reference for local economic empowerment policies in the Serang City area.